An Investigation of Theory of Constraints (TOC) and Related Techniques in Health Care Operations - Ku, Elsa Kui-Chi (2007)
Purpose: Many management concepts, including Total Quality Management (TQM), Six Sigma, Lean and Theory of Constraints (TOC), have been developed over the years. They have been applied by many different organizations in various industries. The most common area of application of the concepts is manufacturing. There has also been an increase usage of the concepts in the service industry, including education, retail, banking and health care services. TOC has been successfully implemented in manufacturing and in many service oriented companies; however, its application in health care is not as common. This paper will discuss the similarities and differences between TOC, TQM, Six Sigma, and Lean, if any, and also investigate the potential reasons to why TOC is not used as much in health care compare to the other concepts.